2010
DOI: 10.3997/1873-0604.2010038
|View full text |Cite
|
Sign up to set email alerts
|

Using integrated near‐surface geophysical surveys to aid mapping and interpretation of geology in an alluvial landscape within a 3D soil‐geology framework

Abstract: An integrated geological, geophysical and remote sensing survey was undertaken as part of the construction of a high resolution 3D model of the shallow subsurface geology of part of the Trent Valley in Nottinghamshire, U.K. The 3D model was created using the GSI3D software package and geophysical techniques used included Ground Penetrating Radar (GPR), Electrical Resistivity Tomography (ERT) and Automated Resistivity Profiling (ARP). In addition, the remote sensing techniques of Light Detection and Ranging (LI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Although the GPR method has shown optimistic results for this type of application, it also presents some limitations. Tye et al (2011) also reported the importance of geophysical surveys for geological mapping of alluvial bodies and the development of the 3D geological models, which contribute to the knowledge of the complexity of sedimentary environments, such as alluvial deposits. Loperte et al (2011) demonstrated that GPR can be a useful tool for the non-intrusive diagnostics of dams and encouraged its use for other defect typologies affecting dams, such as waterproof layer fractures, detachment, and concentrated water infiltration zones.…”
Section: Revmentioning
confidence: 98%
“…Although the GPR method has shown optimistic results for this type of application, it also presents some limitations. Tye et al (2011) also reported the importance of geophysical surveys for geological mapping of alluvial bodies and the development of the 3D geological models, which contribute to the knowledge of the complexity of sedimentary environments, such as alluvial deposits. Loperte et al (2011) demonstrated that GPR can be a useful tool for the non-intrusive diagnostics of dams and encouraged its use for other defect typologies affecting dams, such as waterproof layer fractures, detachment, and concentrated water infiltration zones.…”
Section: Revmentioning
confidence: 98%
“…In other words, the model that best matches the measured data is not necessarily an exact representation of the subsurface parameter distribution. Nevertheless, electrical imaging techniques using either induced or direct current sources have provided promising results for imaging valley morphology (e.g., Jørgensen et al 2003a;Ahmad et al 2009;Steuer et al 2009;Tye et al 2011), and in some cases, the infilled Quaternary sediment architecture (e.g., Baines et al 2002;Leopold et al 2013), particularly when combining multiple geophysical techniques with geological information (e.g., Greenhouse and Karrow 1994;Gabriel et al 2003;Jørgensen et al 2003b;Ahmad et al 2009). …”
Section: Geophysical Investigations Of Buried Valleysmentioning
confidence: 99%
“…Geophysical methods have the capacity to unravel complex geologic relationships and can play a critical role in advancing our understanding of shallow groundwater flow systems in these settings (van Dam 2012). Studies utilizing multiple geophysical methods combined with geologic and hydrogeologic data are particularly effective for 3D mapping of hydrostratigraphic units (e.g., Gabriel et al 2003;Jørgensen et al 2003aJørgensen et al , 2003bSteuer et al 2009; Stumpf and Ismail 2013;Cassidy et al 2014;Sapia et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often the amount of drillings is not sufficient to create detailed models of the geological structure and lithological composition in the subsurface. Incorporation of 2-D and 3-D densely sampled ground-based and/or airborne geophysical data increases the amount of data for subsurface characterisation substantially (Hubbard and Rubin, 2000;Tye et al, 2011). Airborne geophysical techniques offer a quick way of collecting data over a large area in a cost-effective way.…”
Section: Introductionmentioning
confidence: 99%